2019
DOI: 10.1021/acs.jafc.8b05555
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine Red Blotch Virus May Reduce Carbon Translocation Leading to Impaired Grape Berry Ripening

Abstract: Grapevine red blotch virus (GRBV) is suspected to alter berry ripening and chemistry. This study performed a physiological characterization of GRBV infected grapevines with attention to the factors leading to chemical changes during ripening of Cabernet Sauvignon in two rootstocks, 110R and 420A. RB­(+) grapevines had transiently lower net photosynthesis; however, berry total soluble solids (TSS) accumulation was consistently reduced in the two years of study. Accumulation of anthocyanins and loss of titratabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
48
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 47 publications
16
48
3
2
Order By: Relevance
“…RB(+) grapes were 4.2%, 8.2%, and 4.4% °Brix lower than RB(−) grapes at harvest in 2014, 2015 and 2016 seasons, respectively. These results confirmed what was found in other studies regarding the impact of GRBD on grape sugar concentration in red cultivars . The reduced accumulation of sugar has been demonstrated to be one of the most typical impacts of viral diseases in grapevines .…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…RB(+) grapes were 4.2%, 8.2%, and 4.4% °Brix lower than RB(−) grapes at harvest in 2014, 2015 and 2016 seasons, respectively. These results confirmed what was found in other studies regarding the impact of GRBD on grape sugar concentration in red cultivars . The reduced accumulation of sugar has been demonstrated to be one of the most typical impacts of viral diseases in grapevines .…”
Section: Resultssupporting
confidence: 91%
“…Another study showed that berry weight was higher in grape berries from V. vinifera L Albariño grapevines infected by GLRV . However, in Cabernet Sauvignon, no impact was observed regarding berry weight from grapevines infected by GRBV . Unfortunately, the number of berries per cluster was not determined in this study.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations